2019
DOI: 10.1155/2019/3617129
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Developing Hepatocellular Carcinoma following Depressive Disorder Based on the Expression Level of Oatp2a1 and Oatp2b1

Abstract: Background. Accumulating evidence from prospective epidemiological studies has showed that depression disorder (DD) is a risk factor for cancer. The aim of this study is to explore the association of DD and the overall occurrence risk of hepatocellular carcinoma (HCC) and the mechanism. Methods. In this study, 60 mice were randomly divided into four groups: Control group, DD group, HCC group, HCC-DD group. Mice received a chronic dose of reserpine to establish depression model, followed by Diethylnitrosamine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Furthermore, many prospective epidemiological studies have shown that depression is a risk factor for cancer[ 12 , 34 ]. In addition, some studies have confirmed that depression is a risk factor for digestive carcinoma and proposed a mechanism for it[ 35 ]. These innovative explanations provided new ideas for exploring the interaction mechanism of GC and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many prospective epidemiological studies have shown that depression is a risk factor for cancer[ 12 , 34 ]. In addition, some studies have confirmed that depression is a risk factor for digestive carcinoma and proposed a mechanism for it[ 35 ]. These innovative explanations provided new ideas for exploring the interaction mechanism of GC and depression.…”
Section: Discussionmentioning
confidence: 99%
“…SLC13A5, a sodium-coupled citrate transporter, plays a crucial role in hepatic energy homeostasis and hepatoma cell proliferation [ 84 , 85 ]. Organic anion-transporting polypeptides (OATPs) are upregulated in various solid tumors, including liver cancer, with SLCO2A1 (OATP2A1) elevated in HCC and liver metastases from colon cancer, while SLCO1B1 expression decreases in liver cancer, showing a reverse trend with cancer grade [ 128 , 129 ]. There is an increased expression of SLC46A3 reported in HCC patients’ livers [ 12 ]; however, we found that it significantly expresses in the gut region and plays an important role in bacterial muropeptide transportation [ 57 , 130 ].…”
Section: Slc Transporters In Cancermentioning
confidence: 99%
“…Organic anion-transporting polypeptides (OATPs) located in the liver membrane take Gd-EOB-DTPA into hepatocytes, and multidrug resistance-associated protein 2 subsequently excrete it into the biliary tract 5 . Specific food components, drugs, malignancies 6 8 , chronic liver diseases, nonalcoholic fatty liver diseases, liver fibrosis, and inflammation can influence the function and expression of OATPs and alter their pharmacokinetics 9 11 . In type 2 diabetic mice, OATPs expression in hepatocytes is reduced, and Gd-EOB-DTPA uptake by hepatocytes is diminished, leading to a secondary decrease in hepatic signal intensity 12 .…”
Section: Introductionmentioning
confidence: 99%